Pengaruh Desentralisasi Fiskal Terhadap Kemiskinan di Provinsi Jambi - Ernita, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
. This study aims to determine the effect of fiscal decentralization on poverty both partially and simultaneously. It examines factors influencing fiscal decentralization, namely Regional Original Income (PAD), balancing funds, and regional expenditures. The data used in this research are secondary data obtained from the official website of the Directorate General of Fiscal Balance or the Ministry of Finance (DJPK). Based on the discussion results, the conclusions drawn are: 1) There is no significant effect of Regional Original Income on poverty, as evidenced by the t-value of -5.721 < t-table 2.131. 2) There is no significant effect of balancing funds on poverty in Jambi Province, as evidenced by the t-value of 1.399 < t-table 2.131. 3) There is a significant effect of regional expenditures on poverty in Jambi Province, as evidenced by the t-value of 6.22 > t-table 2.131. In conclusion, Regional Original Income and balancing funds do not have a significant effect on poverty, while regional expenditures have a significant effect on poverty in Jambi Province.